Maulana Azad - Datta, V. N. (New Delhi Manohar, 2020)
"Three passions dominated Maulana Azad$1 (Bs life: love of learning, Hindu-Muslim unity and freedom of India. This comprehensive and sensitive study using extensive source material offers, for the first time, a critical portrait of a remarkable intellectual who fought for his country's freedom. He never ceased cultivating his own garden even when as a rebel against British rule he had to live in gaol for about a decade. Shy and reserved by nature and temperamentally a private person who would commune with the minarets of the Taj at Agra in moonlit nights than mix with crowds, this scholar extraordinary was pushed into the arena of political battle and he consecrated his life to the service of the country. Forsaken by his own community and distrusted by others, he never compromised his integrity. Jinnah refused to shake hands with him! In high politics he showed a rare sagacity but his advice was disregarded on some crucial occasions for 'which the country has had to pay a heavy price$1 (B. Towards the close of his life he was a sad man. His thwarted love affair like Dante's had given him a new exalted vision of life. But the ideals he stood for lay shattered and the sense of utter failure in his mission seized him. He never sought fortune and bore sufferings with sangfroid. He complained against none. This work captures the unique spirit of this remarkable personality torn by conflicts and caught up in paradoxical situations. It also provides a sound understanding of those inner turmoils of the man by reviewing them in the broad historical perspective of his times when the destiny of the country which he helped to shape was taking a new turn."s
Keywords: Nation Maker, Social Activist, Great Leader, Maulana Azad